SAWUBONA. A theo-ethic for everyday decolonial gestures - C.J. Kaunda (Acta Theologica)
This article takes a pentecostalicity engagement with the Zulu notion of Sawubona to construct a theo-ethics of everyday decolonial gestures of life-giving, affirmation and enhancing in the context of global coloniality and cultures of death that define and determine life in modern capitalist societies. Pentecostalicity is grounded in the Spirit’s freedom to greet (Sawubona) creation as happened on the Day of Pentecost (Acts 2) with pneumatic gestures of redemption, liberation, emancipation and recognition of the singularity of life and co-becoming of all things in the universe. I demonstrate how indigenous forms of greeting embody pentecostalicity resources that could be mobilised to construct a theo-ethics of everyday decolonial gestures. I underline that such an approach helps to perceive indigenous greetings such as Sawubona as dynamic philosophical terms saturated with incredible meanings deeply rooted in the pro-existential spirituality of care for life.